Endovascular treatment in patients with large vessel occlusion: reduced mortality despite minimal penumbra - Schmidt, Manuel; Breuer, Lorenz; Kallmünzer, Bernd; Schwab, Stefan; Dörfler, Arnd; Engelhorn, Tobias; Hölter, Philip (Neuroradiology, 2019)
Purpose: In patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), endovascular treatment (EVT) is highly effective for emergency revascularization. However, data on functional outcome are lacking for patients, which show no or minimal mismatch between ischemic core and penumbra. Methods: Forty-five patients with AIS due to LVO of the anterior circulation were retrospectively analyzed within 6 h since onset when administered to our department. In all patients, there was no relevant penumbra according to CT perfusion (CTP). Functional outcome, defined by the modified Rankin Scale (mRS) at 30 and 90 days, was analyzed according to LVO treatment (EVT versus non-EVT). Confounding was addressed by multivariable regression analyses. Results: mRS values at 30 days (p = 0.002) and 90 days (p = 0.005) after AIS occurrence were significantly lower in patients who had received EVT. There was no significant difference regarding good functional outcome, as measured by mRS of 0–2 at 30 (p = 0.432) and 90 days, respectively (p = 0.186). Mortality was significantly reduced in patients undergoing EVT at 30-day (p < 0.001) and at 90-day follow-up (p = 0.003), respectively. Multivariable regression analyses revealed that EVT was associated with reduced mortality at 30 (OR 0.091; CI (0.013–0.612); p = 0.014) and 90 days (OR 0.134; CI (0.021–0.857); p = 0.034) after AIS. Conclusions: Despite a small and highly selected patient collective, our study indicates that AIS patients with minimal penumbra in CTP might benefit from EVT in terms of reduced mortality at 30 and 90 days after AIS. However, in this group of patients, we could not prove favorable functional outcome at 30 and 90 days, despite receiving EVT.
CRIS-Team Scopus Importer:2019-09-17
Keywords: CTP; Endovascular treatment; Mortality; Penumbra; Stroke